OS03.4.A In vivo dynamics and anti-tumor effects of EpCAM-directed CAR T-cells against brain metastases from lung cancer. (5th September 2022) - Xu, T; Karschnia, P; Cadilha, B; Dede, S; Lorenz, M; Seewaldt, N; Nikolaishvili, E; Müller, K; Blobner, J; Teske, N; Langer, S; Obeck, H; et al.
Abstract: Background: Lung cancer patients are at a particularly high risk for brain metastases, and a considerable number of affected patients succumb due to their intracranial disease. Chimeric Antigen Receptor (CAR) T-cells emerged as a powerful class of cell-based immunotherapy for hematological malignancies. However, it remains unclear whether CAR T-cells also represent a safe and effective therapeutic option for brain metastases. Material and Methods: A fully syngeneic orthotopic cerebral metastasis model in mice was established by combining a chronic cranial window with repetitive intracerebral two-photon laser scanning microscopy. This approach enabled the in vivo characterization of red fluorescent CAR T-cells and tumor cells on a single-cell level over weeks. Intraparenchymal injection of Lewis lung carcinoma cells (expressing the tumor cell-antigen EpCAM) was performed, and CAR T-cells directed against EpCAM ( EpCAM CAR T-cells) were injected into the adjacent brain parenchyma after solid brain tumors have formed. Results: All mice had visible tumor take four days after the intracranial tumor cell injection, and rapid growth of solitary lesions was seen in the following days. No toxicities mediated by intracranially injected EpCAM CAR T-cells were encountered. In mice treated with EpCAM CAR T-cells, we initially observed substantial CAR T-cell accumulation within the tumor compared to controls (median number: 1700 versus 939 cells/mm 2 ; p = 0.007). This was paralleled by lower velocities of EpCAM CAR T-cells, characterizing T-cell receptor (TCR)-mediated antitumor cytotoxicity due to long-lasting contacts between effector immune cells and tumor cells. Consequently, treatment with EpCAM CAR T-cells resulted in reduced tumorous growth as determined per in vivo microscopy (median tumor area on day 10: 1.8 versus 10.8 mm 2 ; p = 0.001) and immunohistochemistry of excised brains (median tumor volume on day 10: 3.6 versus 33.2 mm 3 ; p = 0.001). However, the number of EpCAM-directed CAR T-cells within the tumor markedly decreased during the observation period, pointing towards insufficient persistence of EpCAM-directed CAR T-cells. In line with these findings, survival was prolonged in mice receiving EpCAM CAR T-cells but long-lasting remission was rare (median survival: 15 versus 13 days; p = 0.012). Conclusion: Our findings indicate that CAR T-cells injected into the cerebral parenchyma may induce relevant anti-tumor effects in brain metastases from lung cancer. Due to the translational nature of our study, prospective clinical cohorts appear warranted. Strategies improving the intratumoral persistence of CAR T-cells in brain metastases may be utilized to further boost the success of such promising therapy.